PENDAMPINGAN PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS KURIKULUM 2013 - Kusumaningrum, Desi Eri; Arifin, Imron; Gunawan, Imam (ABDIMAS PEDAGOGI, 2017)
Abstract: In terms of curriculum change, education in Indonesia to date has undergone several changes in the curriculum. History notes that every change of curriculum, a lot of problems that arise in the world of education. One aspect in the implementation of Curriculum 2013 is the development of learning tools that refers to the Curriculum 2013 policy. The purpose of this assistance is the teacher is able to develop and develop learning tools based on Curriculum 2013. The target audience of making learning tools based on Curriculum 2013 is the teachers of Private Madrasah Ibtidaiyah (Madrasah Ibtidaiyah Swasta / MIS) Lowokwaru Malang. This activity was held in one classroom of MI Al Fattah, with a total audience of 20 target teachers. The method used is varied lectures and exercises. Discourse vary to convey concepts that are important to be understood and mastered by the trainees. Exercises are used to assign tasks to mentoring participants to practice the making of learning tools (focus on lesson plans) based on Curriculum 2013. The results of this activity include several components, namely: (1) the success of the target attendance attendance number of 20 teachers from four MIS Lowokwaru Malang; (2) the achievement of material targets given to the mentoring participants; and (3) the outcome achievement of this mentoring activity is the lesson plan (RPP) made by the teacher.Keywords: mentoring, learning tools, Curriculum 2013Abstrak: Ditinjau dari segi perubahan kurikulum, pendidikan di Indonesia hingga saat ini telah mengalami beberapa kali perombakan pada kurikulum. Sejarah mencatat bahwa setiap pergantian kurikulum, banyak sekali masalah yang timbul dalam dunia pendidikan. Salah aspek dalam implementasi Kurikulum 2013 adalah pengembangan perangkat pembelajaran yang mengacu pada kebijakan Kurikulum 2013. Tujuan pendampingan ini adalah guru mampu menyusun dan mengembangkan perangkat pembelajaran berdasarkan Kurikulum 2013. Khalayak sasaran kegiatan pendampingan pembuatan perangkat pembelajaran berbasis Kurikulum 2013 ini adalah para guru MIS Kecamatan Lowokwaru Kota Malang. Kegiatan ini dilaksanakan di salah satu ruang kelas MI Al Fattah, dengan jurnlah khalayak sasaran adalah 20 orang guru. Metode yang digunakan adalah ceramah bervariasi dan latihan. Ceramah bervariasi untuk menyampaikan konsep-konsep yang penting untuk dimengerti dan dikuasai oleh peserta pelatihan. Latihan digunakan untuk memberikan tugas kepada peserta pendampingan untuk mempraktikkan pembuatan perangkat pembelajaran (fokus pada rencana pembelajaran) berbasis Kurikulum 2013. Hasil kegiatan ini mencakup beberapa komponen yaitu: (1) keberhasilan target jumlah peserta pendarnpingan yang hadir yakni 20 orang guru dari empat MIS Kecamatan Lowokwaru Kota Malang; (2) ketercapaian target materi yang diberikan kepada peserta pendampingan; dan (3) ketercapaian luaran kegiatan pendampingan ini yakni RPP yang dibuat oleh guru.Kata kunci: pendampingan, perangkat pembelajaran, Kurikulum 2013